LOTUS suppresses amyloid β-induced dendritic spine elimination through the blockade of amyloid β binding to PirB - Yuki Kawaguchi; Junpei Matsubayashi; Yutaka Kawakami; Ryohei Nishida; Yuji Kurihara; Kohtaro Takei (BMC, 2022)
Abstract Background Alzheimer's disease (AD) is the most common neurodegenerative disease worldwide but has no effective treatment. Amyloid beta (Aβ) protein, a primary risk factor for AD, accumulates and aggregates in the brain of patients with AD. Paired immunoglobulin-like receptor B (PirB) has been identified as a receptor of Aβ and Aβ-PirB molecular interactions that cause synapse elimination and synaptic dysfunction. PirB deletion has been shown to suppress Aβ-induced synaptic dysfunction and behavioral deficits in AD model mice, implying that PirB mediates Aβ-induced AD pathology. Therefore, inhibiting the Aβ-PirB molecular interaction could be a successful approach for combating AD pathology. We previously showed that lateral olfactory tract usher substance (LOTUS) is an endogenous antagonist of type1 Nogo receptor and PirB and that LOTUS overexpression promotes neuronal regeneration following damage to the central nervous system, including spinal cord injury and ischemic stroke. Therefore, in this study, we investigated whether LOTUS inhibits Aβ-PirB interaction and Aβ-induced dendritic spine elimination. Methods The inhibitory role of LOTUS against Aβ-PirB (or leukocyte immunoglobulin-like receptor subfamily B member 2: LilrB2) binding was assessed using a ligand-receptor binding assay in Cos7 cells overexpressing PirB and/or LOTUS. We assessed whether LOTUS inhibits Aβ-induced intracellular alterations and synaptotoxicity using immunoblots and spine imaging in a primary cultured hippocampal neuron. Results We found that LOTUS inhibits the binding of Aβ to PirB overexpressed in Cos7 cells. In addition, we found that Aβ-induced dephosphorylation of cofilin and Aβ-induced decrease in post-synaptic density-95 expression were suppressed in cultured hippocampal neurons from LOTUS-overexpressing transgenic (LOTUS-tg) mice compared with that in wild-type mice. Moreover, primary cultured hippocampal neurons from LOTUS-tg mice improved the Aβ-induced decrease in dendritic spine density. Finally, we studied whether human LOTUS protein inhibits Aβ binding to LilrB2, a human homolog of PirB, and found that human LOTUS inhibited the binding of Aβ to LilrB2 in a similar manner. Conclusions This study implied that LOTUS improved Aβ-induced synapse elimination by suppressing Aβ-PirB interaction in rodents and inhibited Aβ-LilrB2 interaction in humans. Our findings revealed that LOTUS may be a promising therapeutic agent in counteracting Aβ-induced AD pathologies.